The early treatment strategy of ruptured intracranial aneurysms - Hua-tang YANG; Guang-you LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
The clinical data and therapeutic results of 37 patients with ruptured intracranial aneurysms were retrospectively analyzed, among whom 22 patients underwent endovascular embolization or angioplasty and stenting, and 15 patients underwent clipping of the aneurysms. All of those patients were followed up for 6-12 months after operation. The recovery rate of the former was obviously higher than the latter, while the disability rate was lower. Compared with clipping, endovascular embolization therapy or stenting in the treatment for ruptured aneurysm has a lot of advantages, such as smaller trauma, faster recovery, shorter hospitalization time, high curative effect and safety, achieving satisfactory clinical effect.